2006
DOI: 10.1086/508163
|View full text |Cite
|
Sign up to set email alerts
|

The Discovery of Diffuse X-Ray Emission in NGC 2024, One of the Nearest Massive Star-forming Regions

Abstract: We analyzed deep 75 ks Chandra ACIS-I data of NGC 2024 with the aim of searching for diffuse X-ray emission in this most nearby (415 pc) of massive star-forming regions. After removing point sources, extended emission was detected in the central circular region with a radius of 0.5 pc, and it is spatially associated with this young massive stellar cluster. Its X-ray spectrum exhibits a very hard continuum ( keV) and shows kT 1 8 signs of having a He-like Fe Ka line with a 0.5-7 keV absorption-corrected luminos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Diffuse X-ray emission with a radius of 0.5 pc from the centre of NGC 2024 was reported by Ezoe et al (2006b). The emission has a very hard continuum (kT > 8 keV) and shows a He-like Fe Kα line.…”
Section: A12 Ngc 2024 (The Flame Nebula)mentioning
confidence: 81%
See 2 more Smart Citations
“…Diffuse X-ray emission with a radius of 0.5 pc from the centre of NGC 2024 was reported by Ezoe et al (2006b). The emission has a very hard continuum (kT > 8 keV) and shows a He-like Fe Kα line.…”
Section: A12 Ngc 2024 (The Flame Nebula)mentioning
confidence: 81%
“…Early studies indicated that the detection of diffuse Xray emission in stellar clusters required the presence of stars earlier than O6 (Townsley et al 2003), although an exception, the O7-powered Hourglass nebula (Rauw et al 2002), was known. Ezoe et al (2006b) have since discovered diffuse X-ray emission from NGC 2024 (the Flame nebula), which contains only late O-to early B-type stars. On the other hand, it is curious that diffuse X-ray emission has yet to be detected from some very massive stellar clusters where very early O-type stars are present, such as Trumpler 16 (Wolk et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With significant advances in X-ray observing techniques, diffuse X-ray emission has been detected from many massive star forming regions. Nearby ( < ∼ 2 kpc) samples include RCW 38 (Wolk et al 2002), the Rosette nebula (Townsely et al 2003), M17 (Townsely et al 2003;Hyodo et al 2008), NGC 6334 (Ezoe et al 2006a), NGC 2024 (Ezoe et al 2006b), the Carina nebula (Hamaguchi et al 2007;Ezoe et al 2009;Townsely et al 2011a), the Orion nebula (Güdel et al 2008) and the Cyg OB2 association (Albacete Colombo et al 2018). Their spectra are characterized by multiple-temperature thermal plasma emission with typical plasma temperatures below 1 keV and luminosities of 10 32−35 erg s −1 and some of them (e.g., RCW38, NGC 6334, NGC 2024) also show a hint of a power-law spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Such hard diffuse X-ray emission has been observed from a over a dozen massive star formation regions (e.g. M42 [10], Cyg OB2 [13], Westerlund 1 and 2 [16,17]; see also [19] for a comprehensive list), most of which are also seen at GeV and/or TeV gamma-ray energies.…”
Section: Introductionmentioning
confidence: 99%